Prevention And Law Enforcement Efforts Against The Crime Of Gold Mining Without A Permit (PETI) In The Jurisdiction Of The Merangin Resort Police - Yasmirah Mandasari Saragih; Sumarno Sumarno; Daniel Situmorang; Starting Sihombing; Muhammad Faiz Hadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Illegal mining in Indonesia isn't it things we just heard, In fact, illegal mining has become widespread in almost every region potentially rich in minerals. Illegal mining is the most common found is mining gold. Mining gold illegal or often in short for PETI (Unlicensed Gold Mining) is a mine amount pollution material the mine most tall. In Indonesia, gold mining without a permit is considered an unlawful activity, especially because miners do not have a mining business permit as a business entity. They do not pay taxes and royalties which are sources of state income from mining activities. Their activities also often cause social unrest and environmental damage. One that has gold mines is Jambi Province, precisely in the Merangin Regency area. Gold mines in this district are not only found on land but also in river basins (DAS). Merangin Police have carried out many prevention and law enforcement efforts to deal with mining activities without permits.